The crossmodal correspondences between basic tastes and visual features: examining visual synergies and the underlying psychological mechanisms - Lee, BP (2023)
This thesis presents several explorations on vision-taste crossmodal correspondences, which delve into the patterns, underlying mechanisms, and implications of the systematic associations that have been documented between visual features and basic taste qualities. The research findings presented in this thesis demonstrate the significant role of colour properties, curvilinearity, typeface, geometric configurations, and texture in establishing consensual associations with basic taste qualities. In the previous efforts to identify the possible origins of these correspondences, some promising theories were highlighted by other researchers to explain the causes guiding people to make certain associations between visual and taste attributes. Building on these popular explanations, a theoretical model is proposed that conceptualises the dynamics of crossmodal correspondences, introducing a putative system of hierarchy in decision-making for these associations. The relevant studies featured in this thesis have placed an emphasis on the role of emotion in mediating some of the correspondences observed, and adopted the semantic differential technique to gauge how various feelings associated with sensory attributes might have contributed to the crossmodal correspondences. Experiments in this thesis also reveal that specific pairings of visual features, such as colour and curvilinearity, could work in synergistic ways to influence taste expectations. Finally, the applications of these correspondences in various contexts, from influencing consumer expectations to enhancing dining experiences, are explored with respect to the mapping patterns and potential of visual synergy. The thesis concludes with a reflection on the research achievements, their impact on the field of crossmodal correspondences, the future directions of research in this field, and an acknowledgement of limitations, along with proposals for follow-up studies to address these limitations.